2013
DOI: 10.1177/1535370213497321
|View full text |Cite
|
Sign up to set email alerts
|

MiR-223 modulates multidrug resistance via downregulation of ABCB1 in hepatocellular carcinoma cells

Abstract: Multidrug resistance (MDR) has become a major impediment to a successful treatment for liver cancer patients, and one of the common reasons for MDR is the activation of ABCB1 gene, leading to the over-expression of P-glycoprotein (P-gp), which conferred cancer cells be resistant to a broad range of anticancer drugs. MicroRNAs (miRNAs) are a class of short, non-coding RNA moleculars that can regulate gene expression at the post-transcriptional level. In the current study, the aim is to explore whether miRNA par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 26 publications
(33 reference statements)
4
66
0
Order By: Relevance
“…The re-expression of miR-223 in HBV-, HCV-, and non-HBV-non-HCV-related HCC cell lines revealed a consistent inhibitory effect on cell viability (Wong et al, 2008). Furthermore, Yang et al (2013) demonstrated that miR-223 overexpression plays an important role in the regulation of multidrug resistance (MDR) through downregulation of the ABCB1 expression by increasing the HCC cell sensitivity to anticancer drugs. Therefore, miR-223 may act as a potential therapeutic biomarker for HCC patients who show MDR resistancecaused by increased ABCB1 expression.…”
Section: Mir-223mentioning
confidence: 95%
“…The re-expression of miR-223 in HBV-, HCV-, and non-HBV-non-HCV-related HCC cell lines revealed a consistent inhibitory effect on cell viability (Wong et al, 2008). Furthermore, Yang et al (2013) demonstrated that miR-223 overexpression plays an important role in the regulation of multidrug resistance (MDR) through downregulation of the ABCB1 expression by increasing the HCC cell sensitivity to anticancer drugs. Therefore, miR-223 may act as a potential therapeutic biomarker for HCC patients who show MDR resistancecaused by increased ABCB1 expression.…”
Section: Mir-223mentioning
confidence: 95%
“…Two separate studies show that restoration of miR-122 in HCC cells increases their sensitivity to doxorubicin due to suppression of cell cycle progression, anti-apoptosis effectors and ABC transporter proteins [106,107]. miR-223 was also shown to increase doxorubicin sensitivity by suppressing MDR1 expression in HCC cells [108]. miR-26b is another miRNA that is downregulated in HCC.…”
Section: Molecular Mechanisms Of Doxorubicin Resistancementioning
confidence: 99%
“…In addition, the OS rate of the high miR-221 expression group was significantly lower than that of the low miR-221 expression group [70]. Increasing numbers of miRNAs could be significant biomarkers for the management of HCC (Table 4) [71][72][73][74].…”
Section: Novel Cytokine and Protein Biomarkersmentioning
confidence: 88%